PAST CHANGES IN THE SCOTS PINE FOREST LINE AND CLIMATE IN FINNISH LAPLAND: A STUDY BASED ON MEGAFOSSILS, LAKE SEDIMENTS, AND GIS-BASED VEGETATION AND CLIMATE DATA - Kultti S.; Eronen M.; Mikkola K.; Virtanen T.; Timonen M. (My University, 2006)
Subfossil samples of Scots pine (Pinus sylvestris) and evidence of pine stomata and pollen accumulation rates from previously studied lakes located beyond the present pine forest line in Finnish Lapland were used to reconstruct the extent of the past forest line and the corresponding minimum shift in mean July temperatures, compared with the present. The location of the present pine forest line follows the c. +12.2°C mean July temperature isoline (1961-1990). When minimum shifts in mean July temperatures during the Holocene were studied, the estimated glacio-isostatic land uplift and its regional differences were taken into account. Results indicate that pine reached its maximum distribution between 8300 and 4000 cal. yr BP. The inferred minimum shift in mean July temperature was at that time c. +2.5°C. Until 3000 cal. yr BP, the results indicate a shift of c. +1°C. Between 2538 and 1721 cal. yr BP, evidence for a wider distribution of pine in Finnish Lapland is lacking. During the 'Mediaeval Warm Period' the reconstructed minimum shift in mean July temperature was +0.5°C. The record of subfossil pines beyond the present pine treeline ceases during the initiation of the 'Little Ice Age', c. 700 years ago. © 2006 Edward Arnold (Publishers) Ltd.
Keywords: FINNISH LAPLAND; GIS; HOLOCENE; MEGAFOSSILS; PALAEOCLIMATE; PINE; TREELINE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен